General aspects of Equine Infectious Anemia (EIA) (Research, Society and Development, 2022)
Equine Infectious Anemia (EIA), caused by Equine infectious anemia virus (EIAV), is one of the main viral diseases that affect horses, donkeys, and mules. It is found in all regions of Brazil. The virus is spread by hematophagous insects of the genera Tabanus sp. and Stomoxys calcitrans. EIA is, to date, an incurable disease, and there is no vaccine or treatment for it. Due to its nonspecific clinical signs and the possibility of the presence of asymptomatic infected animals, it is essential periodically to perform serological tests to early detect the animals carrying the virus. Taking into account the severity of EIA, this article aims to discuss some aspects of it, considering the history and epidemiology, characteristics of the etiologic agent, transmission, pathogenesis, clinical signs, diagnosis and consequences, since infected animals can become potential transmitters of EIAV. A bibliographic search was carried out in the Google Scholar, PubVet and Scielo databases, in Portuguese and English, considering the last 22 years. The search terms and descriptors used were "equine infectious anemia" and/or "seroprevalence" and/or "prevalence" and/or "virus" and/or "EIAV" and/or diagnosis. Initially, 40 publications were pre-selected and later, 28 were selected to support this study.